Assessment of drug use pattern using World Health Organization core drug use indicators at Secondary Care Referral Hospital of South India - P Siva Prasad; J Thippe Rudra; P Vasanthi; U Sushitha; M Jaffar Sadiq; G Narayana (Wolters Kluwer Medknow Publications, 2015)
Objectives: The aim of this study was to assess the drug use pattern using World Health Organization (WHO) prescribing, patient care and health facility indicators at Secondary Care Referral Hospital of South India. Methods: A cross-sectional study was conducted at Secondary Care Referral Hospital of South India. WHO core drug use indicators questionnaire was used for the assessment of drug use pattern which comprise of five prescribing care indicators, five patient care indicators and two health facility indicators. 603 patient encounters were reviewed prospectively for a 6 months period from November 2013 to April 2014. Data were collected from outpatients of the pharmacy and results were represented in descriptive statistics. Results and Discussion: The average number of drugs prescribed per prescription was 2.7. The percentage of prescriptions in which antibiotics and injections were comprised about 9.6% (n = 159) and 1.6% (n = 27), respectively. The percentage of drugs prescribed by generic and from essential drug list (EDL) was 42.9% (n = 709), and 95.6% (n = 1578), respectively. The average consulting and dispensing time was 3.7 min and 2.3 min, percentage of drugs actually dispensed and adequately labeled was 96.6% and 99.3%. Percentage of patients had knowledge of correct dosage was 89.3%. The copy of EDL was available and the percentage of key drugs available was 88%. Conclusion: On the basis of above findings, the study was concluded that the prescribing indicators were met WHO standard criteria. The patient care and health facility indicators are rational and the importance of these indicators was encouraged by the doctors and the pharmacists. It shows that available drugs are satisfying unlimited healthcare needs of the public. Further, such studies at different regions of India and their review may produce beneficial results for the betterment of the society.